2013
DOI: 10.1002/hipo.22142
|View full text |Cite
|
Sign up to set email alerts
|

A role for prolyl hydroxylase domain proteins in hippocampal synaptic plasticity

Abstract: Hypoxia-inducible factors (HIFs) are key transcriptional regulators that play a major role in oxygen homeostasis. HIF activity is tightly regulated by oxygen-dependent hydroxylases, which additionally require iron and 2-oxoglutarate as cofactors. Inhibition of these enzymes has become a novel target to modulate the hypoxic response for therapeutic benefit. Inhibition of prolyl-4-hydroxylase domains (PHDs) have been shown to delay neuronal cell death and protect against ischemic injury in the hippocampus. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Moreover, genetic models specific for inactivation of the prolyl hydroxylase domain 2 enzyme exhibit similar deficits in LTP, which cannot be exacerbated by the use of deferoxamine or dimethyloxalyl glycine (Corcoran et al . ). These findings suggest that activation of prolyl hydroxylase domain 2 by iron underlies its observed effects in promoting LTP (Fig.…”
Section: The Role Of Ros In Nmda Receptor‐mediated Plasticity Ltp Anmentioning
confidence: 97%
“…Moreover, genetic models specific for inactivation of the prolyl hydroxylase domain 2 enzyme exhibit similar deficits in LTP, which cannot be exacerbated by the use of deferoxamine or dimethyloxalyl glycine (Corcoran et al . ). These findings suggest that activation of prolyl hydroxylase domain 2 by iron underlies its observed effects in promoting LTP (Fig.…”
Section: The Role Of Ros In Nmda Receptor‐mediated Plasticity Ltp Anmentioning
confidence: 97%
“…We previously showed that application of PHD inhibitors or neuron-specific deletion of PHD2 significantly decreased excitatory postsynaptic potentials and strongly impaired the induction of long-term potentiation [6]. Recently, Segura et al confirmed our hypothesis that PHDs might control neuronal adaptation to hypoxia/ischemia at the level of synaptic activity [7].…”
mentioning
confidence: 69%
“…, Corcoran et al . ). The effects of iron chelation via application of DFO are even greater, decreasing transmission by approx.…”
Section: Effect Of Acute Hypoxia and Hif Stabilizers On Neuronal Signmentioning
confidence: 97%
“…Preliminary work from our laboratory suggests acute and chronic inhibition of PHDs by dimethyloxalyl glycine (DMOG), and DFO impairs synaptic plasticity (long‐term potentiation) in the rat and mouse hippocampus (Corcoran et al . ).…”
Section: Effect Of Acute Hypoxia and Hif Stabilizers On Neuronal Signmentioning
confidence: 97%